Genesis of the Shibaogou Mo–Pb–Zn deposit in the Luanchuan ore district, China: Constraints from geochronology, fluid inclusion, and H–O–S–Pb isotopes - Xu, Yunchou; Wang, Gongwen; Gao, Meng; Yang, Wangdong; Yang, Shuren; Yun, Hui; Wu, Peijian; Guo, Nana; Feng, Yantao (Frontiers in Earth Science, 2023)
The Shibaogou deposit is located in the Luanchuan ore district within the East Qinling orogenic belt (EQOB), central China, which is a newly-discovered Mo-Pb-Zn skarn deposit. The skarn and Mo-Pb-Zn orebodies are mostly hosted in the contact zones between the Shibaogou porphyritic granite and carbonaceous sedimentary rocks from the Luanchuan and Guandaokou sets. A study combined of geochronology, fluid inclusion (FI), and stable isotopes were performed to constrain the mineralization age, source of ore materials, moreover, the origin and evolution of the ore-forming fluids and their relationship with the subduction of the Paleo-Pacific Plate. Mineralization process includes skarn and quartz-sulfide episodes which has four stages: skarn (I), quartz-molybdenite (II), quartz-galena-sphalerite (III), and quartz-calcite (IV). Molybdenite Re-Os dating suggests that the deposit was formed in the Late Jurassic (147.4 ± 7.2 Ma). It has been reported five primary types of fluid inclusions: L-type, V-type, H-type, S-type and C-type. This study found that the ore-forming fluids at the Shibaogou deposit are dominantly magmatic water at the early stage, gradual input of atmospheric water during fluid evolution, with δ18Ofluid values from -1.168 to 8.997‰ and δ18Dfluid values from -106.5 to -79.9‰, based on the O and H isotope data from garnet, quartz and calcite. Furthermore, the S isotopic compositions were measured range from 0.8 to 14.7‰, it demonstrated that the ore-forming fluid were mainly derived from magmatic sources. The relatively homogeneous Pb isotopic compositions are similar to those of shibaogou granite porphyry, it demonstrated that the ore-forming materials were mainly derived from magmatic sources. Molybdenite was precipitated as a result of fluid-rock interactions and fluid boiling, and the galena and sphalerite were precipitated as a result of the decreasing temperature. The subduction of the Paleo-Pacific plate has a critical impact on the complex evolution of ore-forming in the Shibaogou skarn deposit in EQOB.